Natural infection of the sand fly Phlebotomus kazeruni by Trypanosoma species in Pakistan - Kato, Hirotomo (BioMed Central, 2010)
The natural infection of phlebotomine sand flies by Leishmania parasites was surveyed in a desert area of Pakistan where cutaneous leishmaniasis is endemic. Out of 220 female sand flies dissected, one sand fly, Phlebotomus kazeruni, was positive for flagellates in the hindgut. Analyses of cytochrome b (cyt b), glycosomal glyceraldehyde phosphate dehydrogenase (gGAPDH) and small subunit ribosomal RNA (SSU rRNA) gene sequences identified the parasite as a Trypanosoma species of probably a reptile or amphibian. This is the first report of phlebotomine sand flies naturally infected with a Trypanosoma species in Pakistan. The possible infection of sand flies with Trypanosoma species should be taken into consideration in epidemiological studies of vector species in areas where leishmaniasis is endemic.